2014
DOI: 10.1148/radiol.14131601
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Dose Index of Renal Colic Protocol CT Studies in the United States: A Report from the American College of Radiology National Radiology Data Registry

Abstract: Purpose-To determine radiation dose indexes for computed tomography (CT) performed with renal colic protocols in the United States, including frequency of reduced-dose technique usage and any institutional-level factors associated with high or low dose indexes.Materials and Methods-The Dose Imaging Registry (DIR) collects deidentified CT data, including examination type and dose indexes, for CT performed at participating institutions; thus, the DIR portion of the study was exempt from institutional review boar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(64 citation statements)
references
References 31 publications
(37 reference statements)
2
61
0
1
Order By: Relevance
“…In addition, the US Dose Imaging Registry reviewed over 49,000 single-energy urinary tract CT scans and found a mean DLP and effective dose of 746 mGy cm and 11.2 mSv, respectively, a huge increase in ionizing radiation burden in comparison with our results. 18 Our data showed that 28 (26.4%) acquisitions produced a total DLP of under 200 mGy cm and only 23 (21.2%) acquisitions produced a total DLP of over 400 mGy cm, in comparison with USA, in which only 10% of institutions kept DLP at 400 mGy cm or less in at least 50% of patients. 18 Using the abdominal conversion factor reported by the European Guidelines for Multislice Computed Tomography, the mean effective doses for single-energy CT and DECT investigations from our study were calculated as 4.6 and 5.4 mSv, respectively.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In addition, the US Dose Imaging Registry reviewed over 49,000 single-energy urinary tract CT scans and found a mean DLP and effective dose of 746 mGy cm and 11.2 mSv, respectively, a huge increase in ionizing radiation burden in comparison with our results. 18 Our data showed that 28 (26.4%) acquisitions produced a total DLP of under 200 mGy cm and only 23 (21.2%) acquisitions produced a total DLP of over 400 mGy cm, in comparison with USA, in which only 10% of institutions kept DLP at 400 mGy cm or less in at least 50% of patients. 18 Using the abdominal conversion factor reported by the European Guidelines for Multislice Computed Tomography, the mean effective doses for single-energy CT and DECT investigations from our study were calculated as 4.6 and 5.4 mSv, respectively.…”
Section: Discussionmentioning
confidence: 51%
“…[17][18][19] Because of this, low-dose protocols are becoming more widely implemented as the gold standard and have become the standard within our local radiology department. Our study reveals a small but statistically significant increase in radiation dose in patients undergoing DECT over single-energy CT.…”
Section: Discussionmentioning
confidence: 99%
“…24 However, less than 2% of CT scans for renal colic in the United States are conducted with a reduceddose protocol. 25 It is likely that this is due to concern about missing alternative diagnoses, and it has been suggested that reduced-dose (and particularly "ultralow") CT is most appropriately conducted in patients with high likelihood of stone. 26 We believe improved risk stratification of patients with the STONE PLUS algorithm may increase appropriate use of this test.…”
Section: Discussionmentioning
confidence: 99%
“…However, best practices to ensure that the dose is as low as reasonably achievable (ALARA) are not always observed. There is great variation in dose indices across institutions, presumably because of differing Btechnique factors,^such as settings for peak kilovoltage (kVp) and pitch [15]. Even when best practices are observed, outliers must still be detected.…”
Section: Introductionmentioning
confidence: 99%